2010
DOI: 10.1007/s00213-010-1848-1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the acute effects of nicotine and smoking on human performance

Abstract: Rationale and objective Empirical studies indicate that nicotine enhances some aspects of attention and cognition, suggesting a role in the maintenance of tobacco dependence. The purpose of this review was to update the literature since our previous review (Heishman et al. Exp Clin Psychopharmacol 2:345–395, 1994) and to determine which aspects of human performance were most sensitive to the effects of nicotine and smoking. Methods We conducted a meta-analysis on the outcome measures of 41 double-blind, plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
444
8
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(484 citation statements)
references
References 99 publications
(155 reference statements)
23
444
8
9
Order By: Relevance
“…The TT/GG genotype of rs1051730/rs1317286 was associated with decreased PPI levels in both groups (Petrovsky et al 2010). Our findings from that study further support the view that the cholinergic system plays a key role in pre-attentional and attentional mechanisms (Bosch and Schmid 2008;Heishman et al 2010;Hong et al 2008). …”
Section: Introductionsupporting
confidence: 85%
“…The TT/GG genotype of rs1051730/rs1317286 was associated with decreased PPI levels in both groups (Petrovsky et al 2010). Our findings from that study further support the view that the cholinergic system plays a key role in pre-attentional and attentional mechanisms (Bosch and Schmid 2008;Heishman et al 2010;Hong et al 2008). …”
Section: Introductionsupporting
confidence: 85%
“…Smokers commonly believe that smoking improves attention, alertness and concentration (West, 1993) and such perceived benefits have been suggested to motivate continued smoking (Heishman et al 2010). A plethora of studies have demonstrated that smoking can improve, and deprivation impair, performance on a variety of cognitive domains including reaction time (Bates et al 1995;Giannakoulas et al 2003;Perkins et al 1995), vigilance/attention (Bell et al 1999;Gilbert et al 1997), inhibitory control (Powell et al 2001), learning (Soar et al 2008), and working memory (Jacobsen et al 2005;Merritt et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of healthy, non-sleep deprived human subjects have identified both compounds to increase performance in several cognitive domains (Heishman et al, 2010;Linssen et al, 2014). Although there may be ethical concerns surrounding the issue of cognitive enhancement (Hyman, 2011), it is of considerable scientific interest to further investigate the potential of biotechnological interventions to enhance human cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is consistent evidence of nicotinic enhancement of attention in animal models (Hahn et al, 2003) and neuropsychiatric disorders such as attentiondeficit hyperactivity disorder (ADHD), schizophrenia and Parkinson's disease (Kelton et al, 2000;Petrovsky et al, 2013;Poltavski and Petros, 2006), in healthy individuals the enhancing effects on cognitive performance are less pronounced, but confirm positive effects on alertness and attention (Heishman et al, 2010;Sacco et al, 2004).…”
Section: Introductionmentioning
confidence: 99%